Pemanfaatan Media Sosial Instagram pada Akun @Leech_Store sebagai Media Promosi Distribution Outlet (Distro) - Maharani, Berliana; Fitriana, Ana; Widya, Tri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Distribution Outlet (Distro) is currently an attraction for teenagers who like local products through social media promotions to support the growth of Small and Medium Industries (IKM). As time goes by, business people are required to be more innovative, especially when it comes to product promotion via social media. In this case, Leech Store Distro uses social media Instagram as a promotional medium. The formulation of the problem in this research is how to implement aspects Share, Optimize, Manage, and Engage on the use of social media Instagram as promotional media for Distro @leech_store?. The aim of this research is to determine the use of Instagram social media on the @leech_store Instagram account as a promotional medium with four aspects, namely Share, Optimize, Manage, and Engage. This research uses a qualitative method with a descriptive approach. The informants in this study consisted of 2 key informants (Instagram admin @leech_store) and 2 supporting informants (followers @leech_store). The results of this research show that at stage Share, Distro Leech Store has a background in using Instagram to open two-way communication between followers with Distro. On Stage Optimize, Leech Store Distro checks the features mention and tags manually. Level Manage covers media monitoring by checking insight regarding the development of numbers followers manually. At the level of Engage namely building cooperation with brand influencer and Automotive Community.